Raj and the best holiday ever! - Braun, Sébastien (Templar, 2019)
Raj and his dad are going camping. They've packed everything they need and Raj knows they are going to have an amazing time. Once they get there, however, they find they have to contend with wind, rain and a family of very noisy bears
Keywords: Fathers and sons / Children's picture books; Tiger / Children's picture books; Camping / Children's picture books; Fathers and sons; Camping; Tiger; picture books; Picture books; Children's stories / Pictorial works; Livres d'images; Bilderbuch